Biocatalysts in Control of Phytopatogenic Fungi and Methods for Antifungal Effect Detection - Balvantín–García, Cecilia; Gregorio-Jáuregui, Karla M.; Nava-Reyna, Erika; Perez-Molina, Alejandra I.; Martínez-Hernández, José L.; Rodríguez-Martínez, Jesús; Ilyina, Anna (IntechOpen, 2011)
None